THE REASONS ACUTE STROKE PATIENTS NOT RECEIVING THROMBOLYSIS IN AN INDONESIAN REFERRAL HOSPITAL - RASYID, AL; HARRIS, SALIM; KURNIAWAN, MOHAMMAD; MESIANO, TAUFIK; HIDAYAT, RAKHMAD; Rilianto, Beny; SHOLEHA, RATU AZIZAH (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: The aim of this study was to identify reasons acute stroke patients did not receive thrombolysis despite meeting Code Stroke activation criteria in Cipto Mangunkusumo General Hospital during November 2015 until February 2019. Methods: This study retrospectively collected data of adult (aged>18 y old) acute stroke patients admitted to Cipto Mangunkusumo General Hospital from November 2015 to February 2019 who met criteria for Code Stroke activation but did not undergo thrombolysis. Patient’ data were collected from Code Stroke Registry of Cipto Mangunkusumo General Hospital. Results: There were 518 acute stroke patients who had Code Stroke activated in Cipto Mangunkusumo General Hospital from November 2015 to February 2019. 76.3% of acute stroke patients did not receive thrombolytic therapy (n=395). Hemorrhage on computed tomography (CT) scan was the most common reason patients did not receive thrombolysis. The following most common reasons were low or improved National Institutes of Health Stroke Scale (NIHSS) score, family refusal, and exceedance of time window. Conclusion: Hemorrhage on CT scan was the most common reason patients did not receive thrombolysis following by low or improved NIHSS score, family refusal, and exceedance of time window.